Use of TCS3200 sensor to identify heavy metal materials - Kelvin Septa Dewantara; - Yulkifli (PILLAR OF PHYSICS, 2020)
v>Heavy metals are natural components that are toxic and can endanger living things even in a very smallconcentration. Water that is polluted by heavy metals in a certain concentration can harm the ecosystem andcan be fatal if entered the human organ system. The principle of heavy metal concentration measurement usingthe TCS3200 sensor is a sensor will sense the color gradation from dissolved heavy metal. This color gradationwill be calibrated to a concentration of dissolved heavy metals. Heavy metal material that is used for thisresearch were FeCl3, NiSO4, and CuSO4. Based on the analysis results, there were 4 results obtained. The firstone was performance specification from this instrument consists of a TCS3200 sensor, black acrylic box for thesensor placement. In the black acrylic box, there was a hole sample for sample placement. The second result wasthe effect of changing in heavy metal concentration to sensors output data is proportional. The third result wasan instrument calibrating with existing data. The fourth result was accuracy and precision from the instrumentwhich have been calibrated. For FeCl3 material, the average accuracy was 95.5% and precision was 98.7%.For NiSO4, the average accuracy was 96% and precision was 98.3%. For CuSO4 material, the averageaccuracy was 99.7% and precision was 99.8%.